Analysis of Factors Affecting Interest in Using the LinkAja Application in DKI Jakarta - Hana Mutiara Josephine; Chandra Wijaya (Universitas Medan Area, 2022)
This article aims to analyze the factors that influence interest in the use of new technology, especially in the use of digital financial applications. The problem is focused on the acceptance or interest of potential users of the LinkAja application which is the result of a synergy between SOEs to increase financial inclusion in Indonesia. Other privately-owned digital financial applications such as GoPay, OVO, and DANA have received significant acceptance, but this is different from LinkAja even though it has been supported by the BUMN Movement and also the government. To approach this problem, the theoretical reference from Davis's Technology Acceptance Model (TAM) is used (1989) and adds another factor, namely risk perception. The data were collected through Non-Probability Purposive Sampling of as many as 522 samples and processed using the Partial Least Squares method in SEM. and analyzed quantitatively. This study concludes that usage interest is influenced by perceived usefulness, perceived convenience, and user attitudes. Other factors such as risk perception and subjective norms were found to have no significant effect on interest in using LinkAja.